2010
DOI: 10.1097/scs.0b013e3181d841f7
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Accuracy of the 3dMD Photogrammetric System in Craniomaxillofacial Application

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
138
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 32 publications
2
138
0
7
Order By: Relevance
“…In a recent study, 12 reliability of the system was reported to be high, with a mean error of only 0.2 mm. Weinberg et al 20 compared two digital photogrammetry systems with direct physical measurements and found high intraobserver precision across the three methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, 12 reliability of the system was reported to be high, with a mean error of only 0.2 mm. Weinberg et al 20 compared two digital photogrammetry systems with direct physical measurements and found high intraobserver precision across the three methods.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility and accuracy of the technique, has been stated to be "more than sufficient for clinical needs" and has greater accuracy compared with direct anthropometry and 2-D photography. 12 The aim of this prospective clinical trial was to quantify the soft tissue facial changes following RME and to compare these changes with an untreated control group using 3-D facial images. To our knowledge, this study was the first to include a control group to distinguish the changes after RME treatment with those resulting from normal growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Khambay et al 24 found a reproducibility error of ,0.5 mm. Lü bbers et al 25 examined the precision and accuracy of 3D stereophotogrammetry and reported a mean global error between 0.1 and 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The results of that study showed that the system was reliable and had a mean global error of 0.2 mm (range, 0.1-0.5 mm). 19 Losken et al 20 investigated the validation of the 3dMD system's ability to determine volume and found that the relative difference between the measured and calculated volumes was approximately 2%.…”
Section: Discussionmentioning
confidence: 99%